The development of public health in early XXth century in Vilnius - Žalnora, Aistis; Miežutavičiūtė, Vitalija (Acta medica Lituanica, 2014)
Objective. During the interwar period public health went over a difficult metamorphosis. Science of social hygiene developed. Specific researches in the field of social hygiene were done in the Medical Faculty of Vilnius Stephen Bathory University. In this paper we will discuss several global and local social strategies and also several social health policy cases. Methods. In this research we used descriptive and comparative methods. Results. A significant part of papers published by researchers in the Department of Hygiene of the Medical Faculty of Vilnius Stephen Bathory University was intended for social etiology of diseases. It was a characteristic feature of modern hygiene science in Interwar Poland. Since the annexation of Vilnius in 1920, the Polish social hygiene model has been developed in Vilnius. Conclusions. Social medicine studies done in Vilnius Stephen Bathory University are still of significant importance today to the extent of similar social challenges such as cancer, alcoholism, tuberculosis, etc.
Keywords: bacteriology; public health; social hygiene